A Life Interrupted: Essays in honour of the lives and legacies of Christof Heyns - Viljoen, Frans; Fombad, Charles; Tladi, Dire; Skelton, Ann; Killander, Magnus (Pretoria University Law Press (PULP), 2022)
This volume of essays, A life interrupted: essays in honour of the lives and legacies of Christof Heyns, honours Christof Heyns, renowned human rights lawyer, advocate, activist and educator, but also down-to-earth family man, friend and colleague. Christof's sudden and most untimely passing on 28 March 2021 deeply saddened those close to him but also evinced an outpouring of grief from the national and international human rights community. His passing brought a deep sense of loss, in part because, at age 62, he was fully engaged in contributing to the betterment of society and still had so much more to give. His is a life interrupted. But at the same time, looking back over the varied lives he lived, he had already left his mark in so many ways. His influences and impacts are manifold and magical. This collection not only testifies to the legacy that he has left us, but also to the ongoing efforts of many to continue building on his legacy. This collection contains two sets of essays by family members, friends, colleagues, collaborators and students. Part A contains essays of a more reflective and personal nature, while the contributions in Part B link to the scholarly or academic themes Christof had worked on and explored, including international human rights systems, international law, the right to life, freedom of association, international humanitarian law, the impact of human rights treaties, constitutionalism and legal philosophy. However, a neat distinction between the personal and professional is not possible in respect of such a warm, generous and enthusiastic person as Christof. Most of the essays in Part A integrate some of Christof's professional and academic achievements, while many of the essays in Part B also reflect on Christof as a person. The editors, all based at the Faculty of Law, UP, are colleagues and friends who worked closely with Christof. Frans Viljoen succeeded Christof as Director of the Centre for Human Rights. Christof was his doctoral supervisor, mentor and research collaborator. Charles Fombad worked with Christof at ICLA, and took over as ICLA Director after Christof's passing. Dire Tladi, an ICLA fellow, had his office just across from Christof in ICLA. As member of the International Law Commission, he shared with Christof high level engagement with the UN. While Christof served on the Human Rights Committee, his colleague Ann Skelton serves on the Committee on the Rights of the Child. Magnus Killander worked closely with Christof as co-author and co-editor. Christof was also his doctoral supervisor. The publication date of this book is 10 January 2022, which is the date marking 63 years since Christof's birth. The publisher is the Pretoria University Law Press (PULP), of which Christof was also a founder.